International perspectives on improving student engagement : advances in library practices in higher education - Sengupta, Enakshi; Blessinger, Patrick; Cox, Milton D. (Innovations in higher education teaching and learning, 2020)
How can a library engage students and pro-actively create information literacy? What impact might that have? These vital questions are addressed, at an international level, in this timely new book. Delving into various real-life case studies of interventions in colleges and universities from Canada to India, the chapters in this edited collection showcase relevant examples of efforts to improve engagement with library resources. The authors highlight instances of specifically designed student-centered workshops, a university partnership with a writing center, the role of a library in Africa as a source of socio-economic transformation, and many more examples of innovations and collaboration between libraries and students. The experiences shared by authors in this book are a valuable resource for librarians and researchers across the world interested in how their collaborative efforts can promote the value of information literacy and help create opportunities for students to build their library practice skills.